A CRISPR way for accelerating cereal crop improvement: Progress and challenges - Basu, Umer; Riaz Ahmed, Syed; Bhat, Basharat Ahmad; Anwar, Zunaira; Ali, Ahmad; Ijaz, Aqsa; Gulzar, Addafar; Bibi, Amir; Tyagi, Anshika; Nebapure, Suresh M.; Goud, Chengeshpur Anjali; Ahanger, Shafat Ahmad; et al. (Frontiers in Genetics, 2023)
The current food crisis at the global level due to steepness in the human population and vulnerable climatic conditions forced scientists to develop resilient cereal crop plants to attain food security. In this context, we have witnessed the application of targeted mutagenesis by using the versatile CRISPR-Cas systems, since crop improvement through conventional genetic recombination and random mutagenesis are imprecise and result in high off-targeting risks. The accelerated crop improvement using molecular breeding methods based on CRISPR-Cas genome editing (GE) is an unprecedented tool for plant biotechnology and agriculture. The last decade backs the fidelity, accuracy, low levels of off-target effects, and high efficacy of CRISPR technology to induce targeted mutagenesis for improvement of cereal crops. The application of this technology is efficaciously validated in developing stress-tolerant cereal crops such as, wheat, rice, maize, barley, and millets. Since the genomic databases of all these cereal crops are available, several modifications through GE technologies have been deemed to attain desirable results. This review provides a brief overview of GE technologies including an elaborate account of the mechanism and applications of CRISPR-Cas editing systems in inducing targeted mutagenesis of cereal crops for improving desired traits. Further, we have described recent developments in CRISPR-Cas based targeted mutagenesis through base editing and prime genome editing in developing resilient cereal crop plants, possibly providing new dimensions in the field of cereal crop genome editing.